2008
DOI: 10.1262/jrd.19165
|View full text |Cite
|
Sign up to set email alerts
|

Production of Transgenic and Non-Transgenic Clones in Miniature Pigs by Somatic Cell Nuclear Transfer

Abstract: Abstract. Miniature pigs have been recognized as valuable experimental animals in various fields such as medical and pharmaceutical research. However, the amount of information on somatic cell cloning in miniature pigs, as well as genetically modified miniature pigs, is much less than that available for common domestic pigs. The objective of the present study was to establish an efficient technique of cloning miniature pigs by somatic cell nuclear transfer. A high pregnancy rate was achieved following transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 55 publications
1
48
1
Order By: Relevance
“…The different interpretations may have resulted from the variations in species, strains or cell types used in the respective studies. (36). In the present study, the average number of blastocyst cells was significantly lower for the embryos reconstructed using transfected fibroblasts.…”
Section: Discussioncontrasting
confidence: 44%
“…The different interpretations may have resulted from the variations in species, strains or cell types used in the respective studies. (36). In the present study, the average number of blastocyst cells was significantly lower for the embryos reconstructed using transfected fibroblasts.…”
Section: Discussioncontrasting
confidence: 44%
“…In pigs, a signal from three or more embryos is required to maintain pregnancy (King et al, 2002). The pregnancy rate and delivery rate of surrogate females receiving cloned embryos is usually lower than that resulting from transfer of unmanipulated embryos (Hornen et al, 2007;Kurome et al, 2008;Lagutina et al, 2007;Park et al, 2010). The major possible reason for this is that the low developmental ability of cloned embryos significantly reduces their signaling to the recipient mother after embryo transfer, and thus they are unable to cause the recipients establish pregnancy or maintain pregnancy to term.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in strain of the surrogate miniature pig affects the post-implantation development of miniature pig NT embryos [34]. On the other hand, viable cloned [30,35] and transgenic [36] miniature pigs have been produced using domestic pig oocytes as recipient oocytes and surrogate mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of miniature pigs as an animal model has been proven; but nevertheless, only a limited number of studies have reported on cloned miniature pigs derived from somatic donor cells [30,31,[34][35][36]. Because of the comparison with domestic pigs, production of cloned miniature pigs using miniature pigs oocytes has limitations.…”
Section: Lee Et Al 260mentioning
confidence: 99%
See 1 more Smart Citation